2020
DOI: 10.1093/molehr/gaaa031
|View full text |Cite
|
Sign up to set email alerts
|

The SEPT12 complex is required for the establishment of a functional sperm head–tail junction

Abstract: The connecting pieces of the sperm neck link the flagellum and the sperm head, and they are important for initiating flagellar beating. The connecting pieces are important building blocks for the sperm neck; however, the mechanism of connecting piece assembly is poorly understood. In the present study, we explored the role of septins in sperm motility and found that Sept12D197N knock-in (KI) mice produce acephalic and immotile spermatozoa. Electron microscopy analysis showed defective connecting pieces in sper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
5
0
2
Order By: Relevance
“…These data suggest that the upregulated expression and annular localization of sAC are important for sperm capacitation and male fertility. SEPT12 forms complexes in the sperm neck (Shen et al, 2020). In this study, we that SEPT4 was not located in the sperm neck, suggesting that SEPT12 orchestrated septin complexes in the sperm neck were independent of SEPT4.…”
Section: Discussionmentioning
confidence: 61%
“…These data suggest that the upregulated expression and annular localization of sAC are important for sperm capacitation and male fertility. SEPT12 forms complexes in the sperm neck (Shen et al, 2020). In this study, we that SEPT4 was not located in the sperm neck, suggesting that SEPT12 orchestrated septin complexes in the sperm neck were independent of SEPT4.…”
Section: Discussionmentioning
confidence: 61%
“…Two mutations of Sept12 identified in patients disrupted the complex, leading to unstable head-tail junctions and defective connecting piece formation. Strikingly, the mutation of Sept12 and the subsequent disruption of the complex led to loss of Sept10 signal in the annulus (Shen et al 2020) as also observed in Adgb-deficient mice. Accordingly, our data suggest an interdependence between Adgb and Sept10, which is required for the maintenance of the annulus, head shaping and proper mitochondrial localisation.…”
Section: Discussionmentioning
confidence: 65%
“…It is expressed specifically in testis, and located in the neck and annulus regions of mature sperm ( Shen et al, 2017 ). SEPTIN12 forms complexes with other SEPTINs , 1, 2, 10 and 11 at the sperm neck, and 1, 4, 6 and 7 at the annulus, and is essential for the assembly of the connecting pieces and the annulus ( Toure et al, 2011 ; Shen et al, 2017 ; Shen et al, 2020 ). It was first identified as a down-regulated gene in the testicular tissue of infertile men ( Lin et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%